Matrix Metalloproteinases Contribute to Brain Damage in Experimental Pneumococcal Meningitis - Leib, Stephen L. (American Society for Microbiology, 2000)
The present study was performed to evaluate the role of matrix metalloproteinases (MMP) in the pathogenesis of the inflammatory reaction and the development of neuronal injury in a rat model of bacterial meningitis. mRNA encoding specific MMPs (MMP-3, MMP-7, MMP-8, and MMP-9) and the inflammatory cytokine tumor necrosis factor alpha (TNF-α) were significantly (P < 0.04) upregulated, compared to the β-actin housekeeping gene, in cortical homogenates at 20 h after infection. In parallel, concentrations of MMP-9 and TNF-α in cerebrospinal fluid (CSF) were significantly increased in rats with bacterial meningitis compared to uninfected animals (P = 0.002) and showed a close correlation (r = 0.76; P < 0.001). Treatment with a hydroxamic acid-type MMP inhibitor (GM6001; 65 mg/kg intraperitoneally every 12 h) beginning at the time of infection significantly lowered the MMP-9 (P < 0.02) and TNF-α (P < 0.02) levels in CSF. Histopathology at 25.5 ± 5.7 h after infection showed neuronal injury (median [range], 3.5% [0 to 17.5%] of the cortex), which was significantly (P < 0.01) reduced to 0% (0 to 10.8%) by GM6001. This is the first report to demonstrate that MMPs contribute to the development of neuronal injury in bacterial meningitis and that inhibition of MMPs may be an effective approach to prevent brain damage as a consequence of the disease.